(3Mce GHf YWGA Gddg GdScfOQj (B/s - (3RQhb, CMeO Hf eMeO,s 1442-1493; (3GdShjO, fGLj EHQGgjes ((3HjQhJ (B- (3dHfGf (B:s (3GdecJHI GdYUjQjI ,s (3TQcI CHfGA TQja GdCfUGQj ddWHGYI hGdfTQ hGdJhRjY ,s, 2013)
(3jYJHQ cJGH GdMce HeLehYg ef GdMce cJGHG MGadG heKGdG egeG hfgLG eJbfG aj TCf GdJQHjI hJRcjI GdfaS, hGdOdjd Ydi Pdc cKQI LghO GdYdeGA aj TQMg aj GdSGHb hGdMGVQ, abO HdZJ TQhM GdMce eG jRjO Yf KdGKjf TQMG, JDcO HeLedgG YXeI gPG GdcJGH deG jMhj ef efGbH haVGFd hehGYX h JhLjgGJ ddeQjOjf, Ch GdSGYjf aj Sdhc gPG GdOQH(B.s
Keywords: (3GHf YWGA Gddg GdEScfOQj, CMeO Hf eMeO Hf YHO GdcQje,s -- 1260-1309; (3GdJUha s -- (3Mces